MEASURING OF DEPTH PROFILE OF DEFECTS OF HOT ROLLED STEEL SHEET BY IMAGING THE GRATING ON SHEET SURFACE - E. I. Marukovich; Yu. A. Lebedinsky; A. M. Branovitsky; V. Dementjev; Yu. V. Maksimovich (Литьë и металлургия)
The approach to measure defect of mill products during their rolling is considered. the performance of supposed scheme is analyzed for real time conditions.